Nitrogen saturation of forested catchments in central Japan - Progress or recovery?. Issue 1 (2nd January 2022) - Sase, Hiroyuki; Takahashi, Masamichi; Matsuda, Kazuhide; Yamashita, Naoyuki; Tsunogai, Urumu; Nakagawa, Fumiko; Morohashi, Masayuki; Yotsuyanagi, Hiroki; Ohizumi, Tsuyoshi; Sato, Keiichi; Kurokawa, Junichi; Nakata, Makoto
ABSTRACT: Excess inputs of reactive nitrogen (Nr) from the atmosphere will cause disturbances to forest ecosystems, including soil and stream water acidification, plant nutrient imbalances, alterations of species compositions (such as biodiversity losses), and nitrogen (N) leaching into stream water. Central Japan (or Chubu region) has experienced both domestic and transboundary air pollution since the 1950s. Emissions of nitrogen oxides in China peaked in 2011/2012, although the peak of ammonia emissions has not been confirmed. Changes in these emissions have been reflected gradually in atmospheric N deposition rates and the biogeochemical cycle in ecosystems in central Japan. We synthetically analyzed the current N saturation situation for forest ecosystems in central Japan based on our recent publications and the latest available dataset. The stream water in the Lake Ijira catchment (IJR) on the Pacific side in Gifu Prefecture became acidified and N-saturated in the mid-1990s but has begun to recover with a decrease in nitrate (NO3 – ) concentration since the mid-2000s. The progress and recovery of N saturation appeared to be related to the trends of atmospheric deposition, climatic anomalies (such as the cool and drought summers in 1993/1994), and forest management. The NO3 – concentrations in stream water within the forest catchment of Kajikawa (KJK) on the Sea of Japan side in Niigata Prefecture have continued to increase, although the catchment seems to be recovering from acidification owing to a decline in atmospheric sulfur (and probably N) deposition. Finally, the NO3 – concentration in stream water in KJK became higher than that in IJR, a direct inversion of the situation in the early 2000s. The recent analysis of 17 O excess in NO3 – estimated that the export of biologically unprocessed atmospheric NO3 – via stream water was larger in KJK than in IJR. The N cycle in soil-plant systems likely does not function as expected under excess atmospheric N input (still over 10 kg ha –1 year –1 ), especially in KJK. In addition to atmospheric N deposition, reduced N uptake rates as coniferous forests mature, and changing precipitation amounts/patterns appear to accelerate N leaching from forest catchments in central Japan.